2010
DOI: 10.4049/jimmunol.1001421
|View full text |Cite
|
Sign up to set email alerts
|

Homeostatic Turnover of Virus-Specific Memory CD8 T Cells Occurs Stochastically and Is Independent of CD4 T Cell Help

Abstract: Memory CD8 T cells persist by Ag-independent homeostatic proliferation. To examine the dynamics of this cell turnover, we transferred lymphocytic choriomeningitis virus specific memory CD8 T cells into naive mice and analyzed their in vivo division kinetics longitudinally in individual recipients.Using mathematical modeling, we determined that proliferation of this stably maintained memory CD8 T cell population was homogeneous and stochastic with a small fraction of cells completing division at any given time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
89
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(109 citation statements)
references
References 58 publications
10
89
0
Order By: Relevance
“…Choo et al, in a recent paper published in The Journal of Immunology [57], reported the same finding, based on the Ag-independent premise. Choo et al (2010) have determined, by means of a quantitative analysis, that the homeostatic turnover of Agspecific CD8 memory T cells is stochastic rather than deterministic.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Choo et al, in a recent paper published in The Journal of Immunology [57], reported the same finding, based on the Ag-independent premise. Choo et al (2010) have determined, by means of a quantitative analysis, that the homeostatic turnover of Agspecific CD8 memory T cells is stochastic rather than deterministic.…”
Section: Discussionsupporting
confidence: 64%
“…In 2009, Tarlinton et al [49] published a review paper, suggesting that the homeostasis of immune memory can only occur if new memory populations arise over others, i.e., to create dynamic equilibrium among memory cells, some need to disappear for others to arise, because the immune system has a maximum memory capacity [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55]. Choo et al, in a recent paper published in The Journal of Immunology [57], reported the same finding, based on the Ag-independent premise. Choo et al (2010) have determined, by means of a quantitative analysis, that the homeostatic turnover of Agspecific CD8 memory T cells is stochastic rather than deterministic.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we could demonstrate that BrdU can induce proliferation of memory T cells when given orally at a dose of 1 mg per ml in drinking water 10 . Based on our analysis of proliferation using cell cycle ana lysis and Ki67 staining, we feel it is fair to state that the extent of homeostatic proliferation has been largely overestimated previously [3][4][5][6] . We would not be too surprised if it turns out that homeo static proliferation does not have any role at all in the maintenance of memory CD4 + and CD8 + T cells.…”
Section: öZen Sercan Alp and Andreas Radbruchmentioning
confidence: 99%
“…Of mouse memory CD8 + T cells, more than 99% of the cells were in G0 or G1, according to PI staining, with 95% of them being in G0 according to Ki67 staining 10,16 . Both approaches are non invasive and do not involve the manip ulation of cells in vivo, unlike approaches based on bromodeoxy uridine (BrdU) or car boxyfluorescein succinimidyl ester (CFSE) labelling [3][4][5][6] . Indeed, we could demonstrate that BrdU can induce proliferation of memory T cells when given orally at a dose of 1 mg per ml in drinking water 10 .…”
Section: öZen Sercan Alp and Andreas Radbruchmentioning
confidence: 99%
See 1 more Smart Citation